Luminescent Sensor Based on Ln(III) Ternary Complexes for NAD(P)H Detection - Smrčka, Filip; Lubal, Přemysl (Molecules (Basel, Switzerland), 2020)
Ln(III) complexes of macrocyclic ligands are used in medicinal chemistry, for example as contrast agents in MRI or radiopharmaceutical compounds, and in diagnostics using fluorescence imaging. This paper is devoted to a spectroscopic study of Ln(III) ternary complexes consisting of macrocyclic heptadentate DO3A and bidentate 3-isoquinolinate (IQCA) ligands. IQCA serves as an efficient antenna ligand, leading to a higher quantum yield and Stokes shift (250-350 nm for Eu, Tb, Sm, Dy in VIS region, 550-650 nm for Yb, Nd in NIR region). The shielding-quenching effect of NAD(P)H on the luminescence of the Ln(III) ternary complexes was investigated in detail and this phenomenon was utilized for the analytical determination of this compound. This general approach was verified through an enzymatic reaction during which the course of ethanol transformation catalyzed by alcohol-dehydrogenase (ADH) was followed by luminescence spectroscopy. This method can be utilized for selective and sensitive determination of ethanol concentration and/or ADH enzyme activity. This new analytical method can also be used for other enzyme systems coupled with NAD(P)H/NAD(P)+ redox pairs.
Keywords: Catalysis; luminiscence; NAD(P)H determination; macrocyclic ligands; Ln(III) complexes; ethanol; katalýza; alkoholdehydrogenasa; Spectrophotometry; Lanthanoid Series Elements; Molecular Structure; radiofarmaka; antenna ligand; Ethanol; Ligands; molekulární struktura; oxidace-redukce; enzyme probe; Ln(III) luminescence in VIS/NIR range; spektrofotometrie; Oxidation-Reduction; kontrastní látky; Alcohol Dehydrogenase; lanthanoidy; Radiopharmaceuticals; NADP; Luminescence; Contrast Media; ligandy